Symptom patterns and health service use of women in early adulthood: a latent class analysis from the Australian Longitudinal Study on Women’s Health - Louise F. Wilson; Jenny Doust; Gita D. Mishra; Annette J. Dobson (BMC Public Health, 2023)
Abstract Background Symptoms can be strong drivers for initiating interaction with the health system, especially when they are frequent, severe or impact on daily activities. Research on symptoms often use counts of symptoms as a proxy for symptom burden, however simple counts don’t provide information on whether groups of symptoms are likely to occur together or whether such groups are associated with different types and levels of healthcare use. Women have a higher symptom burden than men; however studies of symptom patterns in young women are lacking. We aimed to characterise subgroups of women in early adulthood who experienced different symptom patterns and to compare women’s use of different types of health care across the different symptom subgroups. Methods Survey and linked administrative data from 7 797 women aged 22–27 years in 2017 from the 1989–95 cohort of the Australian Longitudinal Study on Women’s Health were analysed. A latent class analysis was conducted to identify subgroups of women based on the frequency of 16 symptom variables. To estimate the associations between the latent classes and health service use, we used the “Bolck, Croon and Hagenaars” (BCH) approach that takes account of classification error in the assignment of women to latent classes. Results Four latent classes were identified, characterised by 1) low prevalence of most symptoms (36.6%), 2) high prevalence of menstrual symptoms but low prevalence of mood symptoms (21.9%), 3) high prevalence of mood symptoms but low prevalence of menstrual symptoms, (26.2%), and high prevalence of many symptoms (15.3%). Compared to the other three classes, women in the high prevalence of many symptoms class were more likely to visit general practitioners and specialists, use more medications, and more likely to have had a hospital admission. Conclusions Women in young adulthood experience substantially different symptom burdens. A sizeable proportion of women experience many co-occurring symptoms across both physical and psychological domains and this high symptom burden is associated with a high level of health service use. Further follow-up of the women in our study as they enter their late 20 s and early 30 s will allow us to examine the stability of the classes of symptoms and their associations with general health and health service use. Similar studies in other populations are needed to assess the generalisability of the findings.